Integrating minority students through Sekolah Berwatak (Sports-based Character School) Programme: a study of selected secondary schools in the district of Pekan, Pahang - Abd Rahim, Badruel Hairiel; Mohamad Diah, Nurazzura (2012)
The number of minority students who attend mainstream school in Malaysia is substantial. Like the majority students, minority students are required to embrace the agenda of the Malaysian educational system through various programme in order to foster cooperation and unity among students and the school authority. Previous studies have revealed that the experience of minority students in Malaysian schools towards Malaysian educational programme continues to evolve through the years, marking a need for researchers and academicians alike to continuously update their knowledge in this particular field. The objective of this study is to describe the experiences of minority students’ who participate in the sports-based character school (Sekolah Berwatak) programme in selected schools of Pekan, Pahang. To obtain meaningful data for this research, focus group interview (FGI) is employed with a sample of 27 students from the ethnicities of Orang Asli, Cambodian, Rohingya and Chinese. Data analysis was performed using the qualitative process. Our findings have indicated that the sports-based character school programme is seen as a tool for integration and social control in a multicultural environment; elements considered essential by both schools and students. This study provides evidence that students from different ethnic groups are able to work harmoniously with one another during their training sessions and sports competitions. In short, this study is also indispensable to the existing educational researchers who have interest in ethnic relations among minority group in Malaysian schools.